International insertion of contemporary Brazil: the pendulum of changes - Mathias, Meire (2021)
The essay reports to international insertion of Brazil from the 90's, a period in which new strategies were defined economic development for the country, which related changes in the foreign policy. From the Collor government until Lula (1990-2010), the trajectory of change was not straight, whereas the changes in the role of the state corresponded to the definition of strategies for national development, as well as intervening in the course of international insertion of Brazil. Since the early nineties Brazilian governments have decided to implement market-oriented reforms, but, from 2003,puts back certain aspects of industrial policy and therefore alludes to a kind of cautious development of national productive activity. The study does not abandon the consideration of systemic variables for a fuller understanding of the limits and possibilities of international operations of the country, however, rejects the conception of scission between domestic politics and foreign policy.